The Effect of Canva Based Flashcard on Students’ Vocabulary Mastery - Widiarti, Selvia; Qamariah, Zaitun; Normuliati, Sri (Journal of English Language and Education, 2024)
Vocabulary mastery is essential for effective language learning and communication. This research investigates “the effect of canva based flashcards on the vocabulary mastery” of VII class students at MTs Raudhatul Jannah Palangka Raya. This research using quantitative methods and quasi-experimental design, with a sample of sixty students split into experimental class and control classes. The canva based flashcards only used in experimental class. Data was collect from the pretest- posttest and analyzed with a t-test. Pretest scores averaged 61.36 for experiment class and 69.29 for control class. Post test scores increased to 85.88 for experiment class, and 76.69 for control classes. The findings indicate a significant effect of canva-based flashcards on vocabulary mastery. Thus, that's possible be inferred that canva based flashcards effective in significantly increasing studentsvocabulary mastery.